Professional burnout of nursing team working to fight the new coronavirus pandemic - Ana Maria Müller de Magalhães; Denilse Damasceno Trevilato; Daiane Dal Pai; Amanda da Silveira Barbosa; Natascha Monteiro Medeiros; Victória Gabech Seeger; João Lucas Campos de Oliveira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to identify burnout and associated factors among nursing workers working in coping with COVID-19. Methods: a cross-sectional study, developed in four hospitals in a capital in southern Brazil. Sample (n=499) composed of nurses and nursing technicians/assistants, who answered an online form containing socio-occupational characterization and the Maslach Burnout Inventory. Descriptive and inferential statistical analysis was performed, including multiple comparison tests. Results: burnout was identified in 60 (12%) workers, with no significant difference between hospitals, but with a difference in dimensions between them. In the emotional exhaustion dimension, a higher proportion (52.9%) was found at a moderate level. Prevalence of high level of professional achievement of 95.4% was identified. Conclusion: the presence of burnout was significantly prevalent among nurses and females. It reinforces the need to develop strategies to promote the health of nursing workers, providing improvement in health services and reduction of care and labor risks.